2022
DOI: 10.1364/oe.461669
|View full text |Cite
|
Sign up to set email alerts
|

Simple security proof of coherent-one-way quantum key distribution

Abstract: Coherent-one-way quantum key distribution (COW-QKD), which requires a simple experimental setup and has the ability to withstand photon-number-splitting attacks, has been not only experimentally implemented but also commercially applied. However, recent studies have shown that the current COW-QKD system is insecure and can only distribute secret keys safely within 20 km of the optical fiber length. In this study, we propose a practical implementation of COW-QKD by adding a two-pulse vacuum state as a new decoy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Then we have that the gain is simply given by G = τ a G a + (1 − τ a )G ā, where the superscript 'a' indicates that it is calculated for the system that is being attacked all the protocol rounds, as described in section 5, while 'ā' indicates that the metric is calculated in the absence of Eve. The result of G ā can be computed from equation (35)…”
Section: Appendix F Partial Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we have that the gain is simply given by G = τ a G a + (1 − τ a )G ā, where the superscript 'a' indicates that it is calculated for the system that is being attacked all the protocol rounds, as described in section 5, while 'ā' indicates that the metric is calculated in the absence of Eve. The result of G ā can be computed from equation (35)…”
Section: Appendix F Partial Attackmentioning
confidence: 99%
“…that provide lower bounds on the secret-key rate that scale linearly with the channel transmittance η-have been established solely against a restricted class of attacks termed collective attacks [29]. This contrasts with known lower bounds of the order of O(η 2 ) against general attacks [33], a key-rate scaling that has not been improved in recent variants of COW-QKD that disregard its characteristic inter-round interference [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Zeng et al [16] proposed and experimentally verified a QKD protocol that uses mode-pairing to achieve high key rates and robustness against channel noise. Gao et al [17] presented a simple security proof of coherent-one-way QKD, which is a QKD protocol that uses weak coherent pulses and one-way post-processing. Lavie et al [18] improved the coherent-one-way QKD protocol for high-loss channels, by introducing advantage distillation and decoy states.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol has several advantages like the ease of experimental implementation, its robustness against photon number splitting (PNS) attack, it has tolerance against reduced visibility, also it is polarization insensitive. Various research groups have reported the security proofs for COW QKD against general and coherent attacks [18,19]. Being free from PNS attack, this protocol is implementable using attenuated light source which is an advantage as generation of single photon on demand is an extremely challenging task with present experimental resources.…”
Section: Introductionmentioning
confidence: 99%